PENGARUH MULTINASIONALITAS, GOOD COORPORATE GOVERNANCE, TAX HAVEN, DAN THIN CAPITALIZATION TERHADAP PRAKTIK PENGHINDARAN PAJAK PADA PERUSAHAAN MULTINASIONAL YANG TERDAFTAR DI BEI PERIODE TAHUN 2016-2018 - Leony Larasati Widodo; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This study was conducted to determine the effect of multinationality, good corporate governance, tax haven, and thin capitalization on tax avoidance practices in multinational companies listed on the IDX. The sample in this study were 46 Multinational companies that were listed on the Indonesia Stock Exchange 2016-2016. The analytical method used is multiple linear regression. Based on the test results, it can be concluded that simultaneously (multinationality) Multinationality, Good Corporate Governance, Tax Haven, and Thin Capitalization variables have a significant effect on Tax Avoidance. Partial Test Results show that the variable Multinationality, Good Corporate Governance, Tax Haven, and Thin Capitalization have a significant effect on Tax Avoidance.Keywords:Multinationality, Good Corporate Governance, Tax Haven, and Thin Capitalization, Tax Avoidance.